Effect of Vacuum Impregnation on the Quality of Beef Cubes Marinated with Various Natural Meat Tenderizing Agents (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
This study investigates  vacuum impregnation technology, a non-thermal approach to treat local beef cubes (2 cm × 2 cm × 2 cm) with three distinct marinades: distilled water (CONTROL), 10% (v/v) pineapple juice (PINE), and 10% (v/v) papaya juice (PAPAYA), both containing plant proteases (bromelain and papain). The primary objective was to evaluate vacuum impregnation (VI) and traditional marination (TM) techniques and assess their impact on beef’s physicochemical attributes, shelf-life stability, and its plant protease activity. Shelf-life tests over 5 days revealed that all beef samples’ pH reached its lowest on day 4, subsequently increasing on day 5. Throughout storage, colour parameters (L*, a*, b*, and ∆E) of treated samples consistently decreased. VI-PINE exhibited the lowest water holding capacity (WHC) over 5 days. Texture profile analysis (TPA) indicated that VI samples' hardness significantly reduced in VI-PINE and VI-PAPAYA compared to TM samples, attributed to coupled plant proteases. VI-PINE showed the highest marinade uptake improvement (21.6%); while having the lowest WHC (15.52%), and all samples' pH ranged in 5.15–6.12. The colour parameters of treated samples increased compared to raw untreated samples. Compared to TM, VI-PINE (1115 g) and VI-PAPAYA (1333 g) significantly reduced beef hardness, with VI-marinated beef also exhibiting higher tyrosine release compared to TM techniques. The application of VI on beef cubes with plant protease-containing marinades provides practical insights for the food industry, offering potential avenues to enhance beef quality, improve shelf life, and optimize flavour incorporation.
Keywords: Bromelain; Marination; Meat tenderizers; Papain; Shelf-life